A Development of Module for Grade XI Students: A Preliminary Study at SMAN 2 Siak Hulu - Ramadani, Alia; hidayati, Nurkhairo; Yulis, Putri Ade Rahma (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2025)
This study examines teachers' experiences designing instruction, particularly regarding instructional models and teaching materials used in the classroom. The research stems from issues in the field, namely the lack of updated teaching materials such as e-modules. To address this, the researcher interviewed teachers, exploring their teaching experiences and their design and use of teaching materials. The study was conducted at SMA Negeri 2 Siak Hulu in December 2024. Data collection techniques included questionnaires and interviews. The questionnaire data were analyzed using a Likert scale, while interview data were analyzed descriptively. This research employed a mixed-methods design, combining quantitative and qualitative approaches, specifically using a Sequential Explanatory model and an Interpretative Phenomenological Analysis (IPA) approach. The results showed that the questionnaire-based observation sheet indicated a teaching material needs score of 78.2% (high need). Interview findings revealed that teachers' experiences applying the Problem-Based Learning (PBL) model were well-structured and systematic. Moreover, the instructional model was integrated with a Scientific Approach that aligned with the students' characteristics, enhancing learning engagement and improving understanding of science literacy. Teachers perceived that the development of e-modules would greatly support both school-based and independent learning processes.